Why Bahasa Melayu isn't dying - and what it really needs to grow - Mohamad Jamil, Siti Nurnadilla (Sinar Karangkraf, 2025)
Bahasa Melayu's evolution reflects Malaysia’s multilingual reality — its future depends on empowerment, not fear, and investment in digital, education and creative ecosystems.